2016
DOI: 10.4103/1735-3327.192266
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds in regenerative endodontics: A review

Abstract: Root canal therapy has enabled us to save numerous teeth over the years. The most desired outcome of endodontic treatment would be when diseased or nonvital pulp is replaced with healthy pulp tissue that would revitalize the teeth through regenerative endodontics. ‘A search was conducted using the Pubmed and MEDLINE databases for articles with the criteria ‘Platelet rich plasma’, ‘Platelet rich fibrin’, ‘Stem cells’, ‘Natural and artificial scaffolds’ from 1982–2015’. Tissues are organized as three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Interestingly, several in vitro and in vivo studies demonstrated that hMSSM-derived cells are capable of differentiating into cells of osteogenic lineage, thus holding a great clinical promise for better implant-based therapies [24, 25, 36, 37]. Aware that collagen, gelatin, and hydroxyapatite/tricalcium phosphate/Fibrin (HA/ β TCP/Fibrin) scaffolds are characterized by many advantageous features including nonimmunogenicity, biocompatibility, and bioactivity and commonly applied in dental and craniofacial regeneration [3841], we evaluated in this in vitro study the ability of these scaffolds to induce osteogenic differentiation of hMMS-derived cells. This in vitro study could, therefore, simulate the first step of bone regeneration following sinus lift.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several in vitro and in vivo studies demonstrated that hMSSM-derived cells are capable of differentiating into cells of osteogenic lineage, thus holding a great clinical promise for better implant-based therapies [24, 25, 36, 37]. Aware that collagen, gelatin, and hydroxyapatite/tricalcium phosphate/Fibrin (HA/ β TCP/Fibrin) scaffolds are characterized by many advantageous features including nonimmunogenicity, biocompatibility, and bioactivity and commonly applied in dental and craniofacial regeneration [3841], we evaluated in this in vitro study the ability of these scaffolds to induce osteogenic differentiation of hMMS-derived cells. This in vitro study could, therefore, simulate the first step of bone regeneration following sinus lift.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scaffold degradation must be equal to a formation rate of new tissue [42,43]. There are various types of scaffolds known, based on their origin; natural scaffolds (e.g., collagen, hyaluronic acid, PRF, PRP, blood clot, chitosan) and artificial scaffolds (e.g., polymers of polyglycolic acid, polylactic acid, polyepsiloncaprolactone, glass-ceramic, and bioactive glasses) [18,42,44] differ in attributes and properties. Scaffold technology has shown promising advancements in regenerative dentistry, scientifically demonstrated in immunodeficient mice.…”
mentioning
confidence: 99%
“…Therefore, CS is an ideal choice for bone tissue engineering scaffolds, in terms of the initiation of cell recognition, the promotion of cellular adhesion and the formation of M2 phenotype macrophages [ 30 , 31 , 32 , 33 , 34 , 36 , 42 , 43 , 44 ]. However, there are some drawbacks to the use of CS as bone regeneration scaffolds [ 34 , 43 , 45 , 46 ].…”
Section: Application Of Nano-cs In Bone Tissue Engineeringmentioning
confidence: 99%